ANALISA EFISIENSI BOILER DENGAN METODE HEAT LOSS SEBELUM DAN SESUDAH OVERHAUL PT. INDONESIA POWER UBP PLTU LONTAR UNIT 3 - Redaksi Tim Jurnal (Sekolah Tinggi Teknik - PLN, 2017)
One of the main components of the power plant is boiler. Boiler efficiency is very influential on the plant thermal efficiency. To maintain the efficiency of the boiler according to the design need to do maintenance activities, including overhaul. Sankey diagram to do with lack of analysis of the efficiency of the boiler. In this paper to analyze the efficiency of boiler power plant Banten 3 Lontar method of heat loss and Sankey diagram. The results of analysis of boiler efficiency before overhaul 82.78 and after overhaul 83.80%. Compared with the standard design of a drop in efficiency of the boiler before overhaul 10.:38% and 10.18% after overhaul activities. There are three elements to the largest percentage of heat loss which affects the efficiency of boilers that heat loss due to dry flue gas (6.01% -6.11%), heat loss moister fuels (4.9% -5.1%), and loss of heat due to the combustion of hydrogen (3.9% -5.0%). Also from the analysis obtained there are three elements that influence fuel to the formation of heat loss which affects the efficiency of the boiler, this is carbon (46% -52%), humadity moister (27% -33%) and oxygen (11% -13%). Maintenance and overhaul activities significantly affect the boiler efficiency.